The Story the Numbers Tell: A Systematic Review of Phil-IRI Implementation and Outcomes in Philippine Primary Education (2019–2024) - Corog-Jonson, Loida O. (International Journal of Research in Interdisciplinary Studies, 2025)
This systematic review synthesizes empirical research on the implementation and outcomes of the Philippine Informal Reading Inventory (Phil-IRI) in primary education from 2019 to 2024. Following the PRISMA guidelines, a comprehensive search was conducted across electronic databases (Google Scholar, ERIC, Philippine E-Journals), institutional repositories, and relevant government reports. Inclusion criteria encompassed peer-reviewed articles, theses, dissertations, and evaluation reports focusing on Phil-IRI use in Grades 3–6. Data extraction and thematic analysis were performed on the 28 eligible studies. The review identified three major themes: (1) Varied implementation fidelity influenced by teacher training, resource adequacy, and administrative support; (2) Mixed student outcomes, with studies reporting modest gains in reading levels but persistent challenges in moving students from Frustration to Independent levels; (3) Significant disruption and adaptation of Phil-IRI procedures during the COVID-19 pandemic period. While Phil-IRI remains, a cornerstone reading assessment tool, its effectiveness is mediated by systemic enablers and barriers. The findings underscore the need for enhanced teacher professional development, standardized digital adaptation protocols, and stronger policy-practice alignment to maximize its diagnostic and instructional potential.